2018
DOI: 10.1039/c8cc03693d
|View full text |Cite
|
Sign up to set email alerts
|

Highly strained [6]cycloparaphenylene: crystallization of an unsolvated polymorph and the first mono- and dianions

Abstract: An X-ray diffraction study of [6]cycloparaphenylene (1), crystallized under solvent-free conditions, revealed a unique solid state structure with tight packing of individual molecules that minimizes empty internal space. The controlled chemical reduction of this highly strained nanohoop with Group 1 metals resulted in the first isolation and structural characterization of its mono- and dianions, allowing for the evaluation of core transformations for the series ranging from 10 to 11- and 12-.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 46 publications
5
57
0
2
Order By: Relevance
“…An exception is the [6]CPP case, for which three different polymorphs have been found up to date. [19] These findings clearly reveal the subtle yet dominant effect of the weak intermolecular interactions driving the supra molecular self-assembly of these systems. [18] More recently, another polymorph of [6]CPP has been found when the crystallization is carried out by sublimation at 220 °C.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…An exception is the [6]CPP case, for which three different polymorphs have been found up to date. [19] These findings clearly reveal the subtle yet dominant effect of the weak intermolecular interactions driving the supra molecular self-assembly of these systems. [18] More recently, another polymorph of [6]CPP has been found when the crystallization is carried out by sublimation at 220 °C.…”
mentioning
confidence: 89%
“…[18] More recently, another polymorph of [6]CPP has been found when the crystallization is carried out by sublimation at 220 °C. [19] These findings clearly reveal the subtle yet dominant effect of the weak intermolecular interactions driving the supra molecular self-assembly of these systems. [19] These findings clearly reveal the subtle yet dominant effect of the weak intermolecular interactions driving the supra molecular self-assembly of these systems.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…The reaction product exhibited a strongly red‐shifted absorption band ( λ max =600 nm) and the solid‐state structure revealed ionic interactions between the K + ions and both the concave and convex π‐surfaces of [8]CPP . More recently, the same authors reported the one‐ and twofold reduction of [6]CPP , including evidence for the inclusion of THF in the cavity of the nanohoop …”
Section: Metal Coordinationmentioning
confidence: 99%
“…Das Reaktionsprodukt wies eine stark rotverschobene Absorptionsbande auf ( λ max =600 nm), und die Festkörperstruktur zeigte ionische Wechselwirkungen von K + ‐Ionen sowohl mit der konkaven als auch mit der konvexen π‐Fläche von [8]CPP . Vor kurzem berichteten dieselben Autoren über die ein‐ und zweifache Reduktion von [6]CPP , einschließlich dem Beweis für die Einlagerung von THF in den Hohlraum des Nanoreifens …”
Section: Koordination An Metalleunclassified